2006
DOI: 10.1007/s10295-006-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of product capture resin during microbial cultivations

Abstract: Various bioactive small molecules produced by microbial cultivation are degraded in the culture broth or may repress the formation of additional product. The inclusion of hydrophobic adsorber resin beads to capture these products in situ and remove them from the culture broth can reduce or prevent this degradation and repression. These product capture beads are often subjected to a dynamic and stressful microenvironment for a long cultivation time, affecting their physical structure and performance. Impact and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…It has been reported that the positive effects of resin additions to fermentation media are due to the adsorption of non-stable products or to the removal of a product involved in secondary metabolite pathway feedback repression 46 . The addition of polymeric resins to culture media during fungal fermentations induced and/or increased the production of bioactive molecules that were detected in all the assays tested in our screening (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the positive effects of resin additions to fermentation media are due to the adsorption of non-stable products or to the removal of a product involved in secondary metabolite pathway feedback repression 46 . The addition of polymeric resins to culture media during fungal fermentations induced and/or increased the production of bioactive molecules that were detected in all the assays tested in our screening (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, on bacteria and fungi, have described the ability of adsorptive polymeric resins to increase the production titres of certain compounds of microbial origin (Frykman et al 2006 ), and the possible mechanisms of action for these have been reviewed (Phillips et al 2013 ). However, the question of whether one resin is consistently better than others for increasing metabolite chemical diversity has not been examined for any sets of strains.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, high glucose binding observed with Osorb implies that the nutrient binding affects the substrate uptake rate and, therefore, the production and yield in the presence of organo-silica matrices. 26 Furthermore, it has also been reported earlier that organo-silica matrices are known to hinder mass transfer by limiting the rate of diffusion. 27 The pore radius of 90 A in the case of SP70 offers it with an extensive surface area, in contrast to 60 A of Osorb.…”
Section: Extractive Fermentation Using In Situ Adsorbent Resinsmentioning
confidence: 86%